Tinjauan Reflektif Media Massa dalam Pendidikan Politik di Indonesia (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2019)
This article aims to study how the existance and function of political education in Indonesian mass media since Reformation Era.The method used in this article is an inductive approach with library research data collection techniques.This study found that mass media played an important role in political education in Indonesia. The mass media in democracy stateare not only as an information provider, but also as medium of political change of society. The mass media tied to the political system itself. But this study also found the root of the problem of political education in Indonesia was the existence of inequality in the structure of media control in Indonesia so that the media tended to experience deviations and political alignments in reporting. Here we need a reflective moment of political education in the mass media. However, Reformation wave in 1998 was not very encouraging in the development of political education in the mass media. The presence of online media and extensive internet networks was expected to be an alternative to political education but collided with the low level of public literacy. This media alignment cannot be eliminated but can only be minimized by strengthening political education in other sectors such as family, school and society. Even so, mass media still has a significant role in political education but requires a high level of literacy prerequisites.